DOES GEOGRAPHICAL LOCATION MATTER? ASSESSING SPATIAL PATTERNS IN PERCEIVED QUALITY OF LIFE IN EUROPEAN CITIES - ROȘU, Lucian; CORODESCU, Ema; BLĂGEANU, Alexandra (European Journal of Geography, 2023)
The Quality of Urban Life is one of the most important issues of the present policies, being highly researched. The spatial dimension of this concept is still a major challenge for both researchers and policy makers as it was not enough explored and applied. Therefore, the present paper aims to create a more in-depth image on the Quality of Urban Life in Europe, by detecting and explaining the spatial differences in relation to their territorial context. Spatial statistics applied on Urban Audit Data is employed to create a typology of European cities, to identify spatial outliers by using spatial autocorrelation and to map the regional differences in the relationship between different domains of the Quality of Urban Life. Our results bring to light both some clear regional patterns in perception on the Quality of Urban Life and some particular cases - outliers – which require special attention when developing different planning policies. The present research identifies a dominant West-East and North-South gradient, strengthening the idea that QoUL- which has a wide spatial variation- is highly influenced by the geographical location. Hence, the study not only creates a general in depth diagnosis on the Quality of Urban Life in Europe, but also proposes a methodological framework for researching perceptions from a spatial point of view.